2020
DOI: 10.1161/circ.141.suppl_1.55
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 55: Sodium Sensitivity, Sodium Resistance, and Incidence of Hypertension

Abstract: Background: Blood pressure responses to dietary sodium intake vary among individuals. However, it is unknown whether sodium sensitivity and sodium resistance predict incidence of hypertension. Methods: We conducted a feeding study, including a 7-day low-sodium diet (51.3 mmol/day) and a 7-day high-sodium diet (307.8 mmol/day), among 1,718 Chinese individuals with normal blood pressure in 2003-2005 and follow-up studies in 2008-2009 and 2011-2012. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although associations between salt resistance of blood pressure and clinical end points in humans are only just emerging, 10,27–29 functional studies of mice lacking guanylcyclase A and G protein-coupled P2Y receptors have provided not only compelling evidence but a genomic basis, for a salt-resistant model of hypertension. 30,31 Animal research has also long supported genetic mechanisms underlying salt sensitive hypertension.…”
Section: Salt Sensitivity Salt Resistance and Their Clinical Implicat...mentioning
confidence: 99%
See 2 more Smart Citations
“…Although associations between salt resistance of blood pressure and clinical end points in humans are only just emerging, 10,27–29 functional studies of mice lacking guanylcyclase A and G protein-coupled P2Y receptors have provided not only compelling evidence but a genomic basis, for a salt-resistant model of hypertension. 30,31 Animal research has also long supported genetic mechanisms underlying salt sensitive hypertension.…”
Section: Salt Sensitivity Salt Resistance and Their Clinical Implicat...mentioning
confidence: 99%
“…Observational epidemiological research has pointed to high salt sensitivity of blood pressure as an important risk factor for hypertension and ASCVD. 10,[27][28][29] For example, a 2008 report by Barba et al 27 showed that 88% of individuals with high salt sensitivity developed hypertension compared with only 50% of those with lower salt sensitivity (P=0.02). Similarly, Morimoto et al 28 identified a 3-fold increased risk of cardiovascular events among persons with hypertension in the upper blood pressure response to high sodium compared with their counterparts in the lower 90th percentile (P<0.001).…”
Section: Human and Animal Research Of Salt Sensitivity And Salt Resis...mentioning
confidence: 99%
See 1 more Smart Citation